An Experimental Model of Neuromyelitis Optica Spectrum Disorder–Optic Neuritis: Insights Into Disease Mechanisms - Soerensen, Sofie Forsberg; Wirenfeldt, Martin; Wlodarczyk, Agnieszka; Moerch, Marlene Thorsen; Khorooshi, Reza; Arengoth, Dina S.; Lillevang, Soeren Thue; Owens, Trevor; Asgari, Nasrin (Frontiers in Neurology, 2021)
Background: Optic neuritis (ON) is a common inflammatory optic neuropathy, which often occurs in neuromyelitis optica spectrum disease (NMOSD). An experimental model of NMOSD-ON may provide insight into disease mechanisms. Objective: To examine the pathogenicity of autoantibodies targeting the astrocyte water channel aquaporin-4 (AQP4-IgG) in the optic nerve. Materials and methods: Purified IgG from a AQP4-IgG positive NMOSD-ON patient was together with human complement (C) given to wild-type (WT) and type I interferon (IFN) receptor deficient mice (IFNAR1-KO) as two consecutive intrathecal injections into cerebrospinal fluid via cisterna magna. The optic nerves were isolated, embedded in paraffin and cut for histological examination and scored semiquantitatively in a blinded fashion. In addition, optic nerves were processed to determine selected gene expression by quantitative real-time PCR. Results: Intrathecal injection of AQP4-IgG+C induced astrocyte pathology in the optic nerve with loss of staining for AQP4 and glial fibrillary acidic protein (GFAP), deposition of C and demyelination as well as upregulation of gene expression for interferon regulatory factor-7 (IRF7) and CXCL10. Such pathology was not seen in IFNAR1-KO mice nor in control mice. Conclusion: We describe induction of ON in an animal model for NMOSD and show a requirement for type I IFN signaling in the disease process.